MicroRNA-30e-5p Regulates SOCS1 and SOCS3 During Bacterial Infection - Mishra, Richa; Krishnamoorthy, Pandikannan; Kumar, Himanshu (Frontiers in Cellular and Infection Microbiology, 2021)
Host innate immunity is the major player against continuous microbial infection. Various pathogenic bacteria adopt the strategies to evade the immunity and show resistance toward the various established therapies. Despite the advent of many antibiotics for bacterial infections, there is a substantial need for the host-directed therapies (HDTs) to combat the infection. HDTs are recently being adopted to be useful in eradicating intracellular bacterial infection. Changing the innate immune responses of the host cells alters pathogen’s ability to reside inside the cell. MicroRNAs are the small non-coding endogenous molecules and post-transcriptional regulators to target the 3’UTR of the messenger RNA. They are reported to modulate the host’s immune responses during bacterial infections. Exploiting microRNAs as a therapeutic candidate in HDTs upon bacterial infection is still in its infancy. Here, initially, we re-analyzed the publicly available transcriptomic dataset of macrophages, infected with different pathogenic bacteria and identified significant genes and microRNAs common to the differential infections. We thus identified and miR-30e-5p, to be upregulated in different bacterial infections which enhances innate immunity to combat bacterial replication by targeting key negative regulators such as SOCS1 and SOCS3 of innate immune signaling pathways. Therefore, we propose miR-30e-5p as one of the potential candidates to be considered for additional clinical validation toward HDTs.